Group Visits to Improve Pediatric Attention-Deficit Hyperactivity Disorder Chronic Care Management. Issue 8 (October 2015) - Bauer, Nerissa S.; Szczepaniak, Dorota; Sullivan, Paula D.; Mooneyham, GenaLynne; Pottenger, Amy; Johnson, Cynthia S.; Downs, Stephen M.
ABSTRACT: Objective: Children with attention-deficit hyperactivity disorder (ADHD) may experience continued impairment at home and school even after medication initiation. Group visits offer a way for pediatricians to provide more time to address ongoing needs. A pilot study was undertaken to examine whether a group visit model improved ADHD management in the pediatric medical home. Methods: Parents and children aged 6 to 18 years with ADHD were recruited and randomized to group visits or a usual care control. Data included attendance at ADHD follow-up visits, parent-rated ADHD symptoms, adaptive functioning, and quality of life. Longitudinal linear mixed models (continuous variables) and generalized linear mixed models (binary outcomes) were used to compare groups. In our statistical models, child and family were random effects; study assignment was a fixed effect. Results: Twenty families representing 29 children participated (intervention: 9 parents/13 children and control: 11 parents/16 children). Aside from race, baseline characteristics of participants were similar. None of the intervention families missed the expected 5 ADHD follow-up visits over 1 year; control families missed 1 or more visits over the same period. Intervention families reported an improved level of adaptive functioning at 12 months compared with control (mean severity score: 3.7 vs 4.4, p = .003). All families reported greater limitations and poorer quality of life compared with national norms. Conclusion: Group visits in the pediatric medical home can improve adherence, and preliminary results show a variety of improvements for the family.